Charakterystyka form sprzedaży bezpośredniej preferowanych przez podkarpackich producentów rolnych - Dziedzic, Sylwia; Woźniak, Leszek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The article presents, as first in our country, a broad review of definitions quoted by foreign references as well as typology for direct sales forms of agricultural products. The second part of this article discusses the results of own research on direct sales forms that are preferred by Subcarpathia direct salers. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 315-321